Mortgage Rights for The Sharia Banking Murabahah Akad its Position and Application - Ayup Suran Ningsih; Rini Fidiyani; Harumsari Puspa Wardhani (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This research aims to explain the practice of mortgage rights in Islamic banking, the legal position of mortgage rights as a form of collateral in Islamic banking financing, the application/implementation of mortgage rights in Islamic banking financing, and explore whether mortgage rights as a form of collateral in Islamic banking financing have an equal position with credit in conventional banking. This research uses a sociolegal approach with secondary data sources, namely a review of primary legal texts, secondary legal literature, and non-legal sources. This research concludes that: 1) Mortgage Rights' validity in Islamic banking financing can be observed through the institution of Mortgage Rights regulated in Law Number 4 of 1996 concerning Mortgage Rights on Land and Related Objects. 2) In Islamic banking practice, there is a strong emphasis on the existence of collateral in the assessment of providing financing to customers. 3) Mortgage rights as collateral have a different position between conventional and Islamic banks. This research contributes to understanding the legal position and application of mortgage rights as collateral in murÄbaá¸¥ah contracts in Islamic banking. It compares it with the credit system in conventional banking. The research results are expected to provide policy references in the banking sector regarding more effective implementation of mortgage rights in murÄbaá¸¥ah contracts.